2015
DOI: 10.1024/1012-5302/a000411
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring von Pflegekontextfaktoren – Erste deskriptive Studienresultate einer Querschnittserhebung der schweizerischen DRG Begleitforschung Pflege vor Einführung der SwissDRG

Abstract: The study has provided the participating hospitals with useful data upon which to base discussions on ensuring quality of nursing care and practice development, in addition to information important to the further development of the model and the instruments employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…The descriptive quantitative results are shown in Table . These results are described in detail in an earlier publication (Kleinknecht‐Dolf, Spichiger, et al., ). The Rasch analysis indicated differential item functioning (DIF) of several items.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…The descriptive quantitative results are shown in Table . These results are described in detail in an earlier publication (Kleinknecht‐Dolf, Spichiger, et al., ). The Rasch analysis indicated differential item functioning (DIF) of several items.…”
Section: Resultssupporting
confidence: 64%
“…Given its many possible causes, the prevalence of moral distress is high. According to recent studies, nearly 47% of nurses in acute care hospitals often experience situations that trigger moral distress (Kleinknecht-Dolf, Spichiger, et al, 2015;Ulrich, Lavandero, Woods, & Eerly, 2014;Woods, Rodgers, Towers, & La Grow, 2015).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…As empirical evidence, twelve studies were classified in which instruments such as self-developed questionnaires [ 32 , 33 ] or single items [ [34] , [35] , [36] , [37] ] were used to measure readiness for discharge, for which no German or English language validation study could be identified. One of the 33 validated instruments was a single item [ 38 ] and the other was a German translation of the Readiness for Hospital Discharge Scale/Short Form [ 39 ]; however, according to the authors, further studies on the concept of patient readiness to leave the hospital as well as assessing the validity and reliability of the questionnaire are needed before the instrument can be used systematically. Owing to these results, neither study was included in the systematic overview of the validated instruments for readiness to discharge measurement instruments in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Altruism is nurses' most important work value ( 24 26 ), but recent research postulates improvements in nurses' burnout symptoms with altruistic work values ( 11 ). However, studies also found that in the sense of moral stress ( 27 ), the gap between professional ideals and working reality may lead to burnout ( 28 , 29 ). We assume this gap between nurses' altruistic motives and the working conditions that do not allow helping others adequately.…”
Section: Introductionmentioning
confidence: 99%